Serbian Hotel Industry Development - Pavlović, Dejana; Lazić, Jelena; M. Cvijanović, Janko (Hotel and Tourism Management, 2014)
Investing in hotel industry is of immense importance for developing countries. The Republic of Serbia has both potential and opportunities for tourism development. One of the advenatages is its favorable territorial position of the country at the intersection of the main roads of Europe and Asia. In this way, Serbia has become very popular destination for Western Europe tourists over the past few years. In the last ten years, investments in hotel industry increased after arrivals the most popular hotel chains. This study aims at providing an overview of previous investments in the hotel industry and analyzing the needs for high category hotels. Special attention was paid to Crowne Plaza Hotel which appeared in the market in December, 2013 and contributed to the development of economic growth in Serbia.